Microphase separation and aggregate self-assembly in brushes of oppositely charged polyelectrolytes triggered by ion pairing - Debais, Gabriel (2020)
This work applies a molecular theory to study the formation of lateral self-assembled aggregates in mixed brushes composed of polyanion and polycation chains. In order to overcome the well-known limitations of mean-field electrostatics to capture polyelectrolyte complexation, the formation of ion pairs between anionic and cationic groups in the polyelectrolytes is explicitly modeled in our theory as an association reaction. This feature is essential to capture the microphase separation of the mixed brush and the formation of lateral aggregates triggered by polyelectrolyte complexation. The effects of solution pH and ionic strength, surface coverage, and chain length on the morphology of the mixed brush are systematically explored. It is shown that increasing salt concentration leads to the rupture of polyelectrolyte complexes and the stabilization of the homogeneous, non-aggregated brush, providing that the formation of ion pairs between the polyelectrolytes and the salt ions in solution is explicitly accounted for by the theory. The inclusion of ion-pairing association reactions between oppositely charged polyelectrolytes within a mean-field description of electrostatics emerges from this work as a useful and simple theoretical approach to capture the formation of polyelectrolyte complexes and their responsiveness to solution ionic strength and pH.